Benefits and risks of preoperative bowel cleansing in the pediatric population - Cordero Castro, Silvia (2013)
This article has as aim to announce the results of a clinical question referred about the intestinal cleanliness method most adapted for the pediatric population before a colorectal surgery, in order to diminish the electrolytic alterations for the utilization of the same ones and hereby to provide a better intestinal preparation with the minor risks. Is true the method of intestinal cleanliness it is a medical indication, the infirmary professionals must think about his work and wonder it brings over of his own practice and to work in a surest way (Young, 2003). There was realized a search, review and analysis of the scientific literature for that there were use different databases, as for example seeker academic GOOGLE, administrators of articles PUBMED, MEDLINE, EMBASE, SCIELO and Cochrane in Spanish and English language. Found 31 investigations that refer to the interest topic in indirect form. The conclusion were that the fosfosoda oral is effective and better tolerated in the intestinal cleanlinesses with the exception of the magnesium citrate who overcomes in flavor, for this could be an option for the use in pediatric populations. Nevertheless to use cautiously it's recommended to take renal function test and electrolytic pre, trans and post administration, added to the use of intravenous solutions mixed or electrolytic balanced intravenous as reinstatement to the losses. Nevertheless, there is no forceful evidence to determine which method of intestinal cleanliness is better and less risky for the children.